THE USE of DIRECT SOLAR ENERGY in ABSORPTION REFREGERATION EMPLOYING NH3 – H2O SYSTEM - A. Al-Hemiri, Adel; Deaa Nasiaf, Ahmed (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
This work was conducted to study the coefficient of performance for solar absorption refrigeration by using direct solar energy using aqueous ammonia 0.45 mass fraction (ammonia – water).The experiments were carried out in solar absorption system .The system consisted of solar collector generator (0.25 m × 0.25 m × 0.04m) and condenser cooled by a water bath followed by liquid receiver and evaporator. The results showed that the maximum generator temperature was (92° - 97°) during June 2009, and the minimum evaporator temperature was (5°C - 10°C) for aqua ammonia system.. It was, also, found that the coefficient of performance, cooling ratio and amount of cooling obtainable increased with increasing maximum generator temperature and pressure. While the minimum evaporator temperature and concentration decreased with increasing maximum generator temperature and pressure. The coefficient of performance was (0.1096 - 0.2396).